Differentially expressed proteins and microbial communities of the skin regulate disease resistance to Chinese tongue sole (Cynoglossus semilaevis) - Wang, Lei; Tian, Min; Chen, Songlin (Frontiers in Immunology, 2024)
Vibriosis, caused by Vibrio, seriously affects the health of fish, shellfish, and shrimps, causing large economic losses. Teleosts are represent the first bony vertebrates with both innate and adaptive immune responses against pathogens. Aquatic animals encounter hydraulic pressure and more pathogens, compared to terrestrial animals. The skin is the first line of defense in fish, constituting the skin-associated lymphoid tissue (SALT), which belongs to the main mucosa-associated lymphoid tissues (MALT). However, little is known about the function of immunity related proteins in fish. Therefore, this study used iTRAQ (isobaric tags for relative and absolute quantitation) to compare the skin proteome between the resistant and susceptible families of Cynoglossus semilaevis. The protein integrin beta-2, the alpha-enolase isoform X1, subunit B of V-type proton ATPase, eukaryotic translation initiation factor 6, and ubiquitin-like protein ISG15, were highly expressed in the resistant family. The 16S sequencing of the skin tissues of the resistant and susceptible families showed significant differences in the microbial communities of the two families. The protein-microbial interaction identified ten proteins associated with skin microbes, including immunoglobulin heavy chain gene (IGH), B-cell lymphoma/leukemia 10 (BCL10) and pre-B-cell leukemia transcription factor 1 isoform X2 (PBX2). This study highlights the interaction between skin proteins and the microbial compositions of C. semilaevis and provides new insights into understanding aquaculture breeding research.